Maternal cohort, time of stillbirth, and maternal age effects in Italian stillbirth mortality. Issue 2 (June 1990) - Parazzini, F; La Vecchia, C; Mezzanotte, G; Fedele, L
Abstract : STUDY OBJECTIVE–The aim of the study was to investigate factors in stillbirth mortality in Italy. DESIGN–Italian stillbirth data from 1955 to 1979 were analysed using a log-linear Poisson model with arbitrary constraints on the parameters to identify the effects of maternal birth cohort, calendar period of stillbirth and maternal age. SETTING–Stillbirth data for the whole of Italy were obtained from the Italian Central Institute of Statistics for the years under examination. During this period the criteria for defining stillbirth did not change and the quality of birth registration was similar. MAIN RESULTS–Decreases in stillbirth mortality were marked and steady, starting for the generations born since 1920. A period effect in stillbirth trends was shown, but this was apparently smaller than the cohort trend. CONCLUSIONS–The cohort trend suggests that long term improvements in socioeconomic and general health conditions may be important factors in the diminishing stillbirth rates, as well as short term advances in obstetric care. Alternatively the cohort effect could be attributed, at least in part, to an age-period interaction, since the downward trends were more pronounced in younger women.